A study on foster care placement breakdown using rational choice theory - Blodgett, Rebecca C. (Kansas State University, 2022)
Foster placement breakdown, wherein foster parents request the removal of their foster children, is detrimental to foster children and is linked to increased behavioral problems, poor academic growth, and housing instability later in life. This study utilized rational choice theory to explore how child (age, gender, race, health, behavior, history of sexual abuse victimization), foster family (number of caregivers, income), and case (TPR status) characteristics affect foster parents' decision-making processes regarding placement breakdown. A secondary analysis was performed on data from the National Survey on Child and Adolescent Well-being II (NSCAW II), a longitudinal study that followed 5,873 children from 83 counties in 30 states, to determine the extent to which child, foster family, and case characteristics are correlated with placement breakdown and potential placement breakdown in the future. A subsample of 280 cases was used. Logistic regressions indicated that in agreement with the hypothesis, each additional year of child age is correlated with a 19.0% (95% CI [1.050, 1.347]) increase in odds of actual placement breakdown and a 10.3% (95% CI [1.022, 1.190]) increase in odds of potential placement breakdown. It was also found that, in disagreement with the hypothesis, for children who had one biological parent with legal parental rights, the odds of potential placement breakdown (i.e., the unwillingness of foster caregivers to continue caring for children long-term) were 0.253 times (95% CI [0.114, 0.559]) that of children who had no biological parents with legal parental rights. No other significant relationships were found, indicating that rational choice theory applied to these data cannot fully explain why placement breakdown occurs.
Keywords: Foster placement breakdown; Rational choice